Impact of dialysis reimbursement policies on care outcomes in peritoneal dialysis patients in Taiwan. (June 2023) - Chang, Ray-E; Lin, Shih-Pi; Myrtle, Robert C.
Highlights: Public policies designed to change practice behaviors should be evaluated for unintended consequences. Public policies that increase patient responsibilities for self-care need to ensure the patient's ability to do so. Expanding practice behaviors may require different provider and resource competencies. When experience with a treatment is not widespread, increasing utilization may require policy support. Public policies that require changes in provider behaviors should not automatically assume past experience implies an ability to do more quickly or easily. Abstract: The number of treated end stage renal disease (ESRD) patients worldwide has rapidly grown. To prolong their lives ESRD patients require transplantation or dialysis treatment. Limited donor availability has caused most of the ESRD patients to rely on either hemodialysis (HD) or peritoneal dialysis (PD). Taiwan had the highest prevalence rate worldwide and sought to increase the PD utilization through a series of reimbursement incentives. This study evaluated the effect of those policy initiatives. A retrospective longitudinal study using a before-and-after analysis was conducted. ESRD patients initiating either PD or HD were identified from the entire population of Taiwan NHI's beneficiaries. PD patients, before and after the PD-encouraging initiatives, were matched through a propensity score technique, and the change in PD technical failure was analyzed. HD patients were also matched as the control group to assess the impact on PD mortality. The competing risk regression approach for survival analysis was adopted. The results indicate the increase in PD utilization during this period was also accompanied by increases in both technique failure and mortality. Since PD shifts more burden of care to patients, efforts to increase its utilization may require an increase in the education of providers and patients to benefit more effectively. It may also require an increase in staff to provide ongoing training and support as the policy unfolds.